Image artefacts in industrial computed tomography - Horvatić Novak, Amalija (Array, 2020)
Computed tomography is a method that has been used for many years in medicine and material analysis, and recently it has also been introduced in dimensional measurements. The method has a lot of advantages compared to other 3D measurement methods, with the largest one being the possibility to perform a non-destructive measurement of an object’s inner geometry. However, it is a complex method with a large number of parameters that influence measurement results. Some of these parameters are image artefacts that occur in the scanning and reconstruction process. An artefact is any artificial feature which appears on the CT image, but does not correspond to the physical feature of an object. In order to achieve metrological traceability, it is necessary to eliminate and minimize the influence of image artefacts on measurement results. This paper presents and explains image artefacts in industrial computed tomography as the consequences of different influence parameters in the CT system.